A Demand-Side View of Risk Adjustment - Roger Feldman; Bryan E. Dowd; Matthew Maciejewski (SAGE Publishing, 2001)
This paper analyzes the efficient allocation of consumers to health plans. Specifically, we address the question of why employers that offer multiple health plans often make larger contributions to the premiums of the high-cost plans. Our perspective is that the subsidy for high-cost plans represents a form of demand-side risk adjustment that improves efficiency. Without such subsidies (and in the absence of formal risk adjustment), too few employees would choose the high-cost plans preferred by high-risk workers. We test the theory by estimating a model of the employer premium subsidy, using data from a survey of large public employers in 1994. Our empirical analysis shows that employers are more likely to subsidize high-cost plans when the benefits of risk adjustment are greater. The findings suggest that the premium subsidy can accomplish some of the benefits of formal risk adjustment.